Residential building stock legacy of post-Yolanda recovery. IN Disaster resiliency [column] observations from select communities in Samar and Eastern Samar - Tumamao-Guittap, Geomilie S. (United Architects of the Philippines Journal, 2017)
The Philippine is regarded as one of the world's disaster-prone countries reflecting both its high incidence of natural hazard events and significant vulnerability. Cutting a deadly path across Visayas, the scale and magniture wrought by typhoon Yolanda (international name: Haiyan) warranted the declaration of a "state of calamity" to hasten response, recovery and rehabilitation efforts of the government and the private sector, including international humanitarian aid. In response to the worldwide appeal for support, funds from different sources and all corners of the world poured in for Yolanda survivors.